Patterns and Covariates of Age at First Birth In Botswana: Duration Analysis Approach - Kidane, Asmerom; Bariagaber, Hadgu (Tanzania Journal for Population studies and Development, 2012)
The paper considers the covariates of age at first birth in Botswana. It reviews the conceptual issues on the relation between age at first birth and fertility, and then summarizes the socio-economic and demographic situation of the country. The specific objective of the study was to see the relation between age at first birth and fertility. Once the relation was specified and estimated, it used Event History Analysis or Survival Function to determine the pattern of age at first birth, followed by estimating and comparing variation in survival function by the level of education, income and residence. Thereafter it applied the Cox Proportional hazard to see the effect of the three covariates together on the age at first birth. The findings show that there is a significant negative relation between age at first birth and fertility as measured by children ever-born (CEB). The overall conclusion suggests that delayed age at first birth as having a substantial impact on depressing fertility. From the study one is able to predict that if a mother’s age at first birth is increased by ten years, fertility as measured by children ever born will decrease by 12%, a significant reduction. This is likely to have positive impact on the welfare of mothers and children.